Pengelolaan Minyak Jelantah Sebagai Sarana Pengembangan Usaha Berbasis Komunitas Masyarakat RW 10 Kelurahan Tanjungrejo Kecamatan Sukun Kota Malang - Michael Gerits Kriswanto Remetwa; Vinno Chrismantara (Akubis : Jurnal Akuntansi dan Bisnis, 2024)
Sustainable development programs in community life can enhance the welfare of the people in Malang City, especially in Rukun Warga 10, Tanjungrejo Village. Applying the community-based economic empowerment model sustainably can yield a significant positive impact. This research aims to illustrate how to manage used cooking oil waste as a community-based initiative that benefits both the economy and the environment. The focus of this research is the Kios Berkat Jelantah (Betah) Gempol Marga Bakti (Gemati) program, with an emphasis on descriptive data analysis. The results show that active collaboration between various parties, such as local communities, village officials, and educational institutions, encourages community participation in collecting and processing the used cooking oil into value-added products like soap and candles. This program has a positive impact on environmental preservation and provides new economic opportunities for local residents.